2016
DOI: 10.1016/j.drudis.2015.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Conformational stability and self-association equilibrium in biologics

Abstract: Biologics exist in equilibrium between native, partially denatured, and denatured conformational states. The population of any of these states is dictated by their Gibbs energy and can be altered by changes in physical and solution conditions. Some conformations have a tendency to self-associate and aggregate, an undesirable phenomenon in protein therapeutics. Conformational equilibrium and self-association are linked thermodynamic functions. Given that any associative reaction is concentration dependent, conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…The peak at 230 nm is suggestive of aggregation or disordered proteins. This disordered conformation is unstructured to partially structured, dominated by random coils and pre-molten globules, 59 and similar to intrinsically disordered proteins (IDPs) which are without a regular secondary structure or have an absence of a three-dimensional structure and is detected by CD as “random coil”, “unordered”, or “disordered”. This study may be extrapolated to some IDPs or provide some clues to diseases caused by protein misfolding.…”
Section: Discussionmentioning
confidence: 99%
“…The peak at 230 nm is suggestive of aggregation or disordered proteins. This disordered conformation is unstructured to partially structured, dominated by random coils and pre-molten globules, 59 and similar to intrinsically disordered proteins (IDPs) which are without a regular secondary structure or have an absence of a three-dimensional structure and is detected by CD as “random coil”, “unordered”, or “disordered”. This study may be extrapolated to some IDPs or provide some clues to diseases caused by protein misfolding.…”
Section: Discussionmentioning
confidence: 99%
“…Biologics have reduced toxic side effects compared to traditional antineoplastic drugs; however, they can overstimulate the immune system, leading to toxicity and inflammation [ 9 , 10 , 11 ]. Additionally, as biologics are mostly composed of proteins and nucleic acids, a change in conformation impairs their function, and they are susceptible to chemical and enzymatic degradation [ 12 , 13 ]. Well-engineered nanocarrier-based DDSs should enhance efficacy and reduce side effects by (1) protecting payloads from degradation and extending their circulation half-lives, (2) enhancing preferential uptake by tumor cells and reduce uptake by non-cancerous cells, and (3) releasing the active payload only when an appropriate stimulus is applied.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the reversibility of unfolding of these proteins in different formulation conditions might vary 37,40,41 . Recently, it was suggested that one could use ICD experiments to investigate non-reversibility effects during protein unfolding in a denaturant 47,48 . Such experiments study how the apparent Gibbs free energy of protein unfolding changes when different protein concentrations are used to obtain the ICD curves.…”
Section: Introductionmentioning
confidence: 99%